The First Application of Positron Emission Tomography/ Magnetic Resonance Imaging in Russia - A. S. Chaban; S. G. Mirzoyants; M. R. Kalinin (Вестник рентгенологии и радиологии)
PET/MRI is a new hybrid imaging technique that involves all achievements of modern magnetic resonance imaging (MRI) and positron emission tomography (PET). PET/MRI has advantages over other imaging methods and will most likely soon become the gold standard for visualization in some areas of radiodiagnosis. This clinical case demonstrates  the  first application  of PET/MRI  in Russia in a patient  with multiple endocrine neoplasia type 1. PET/MRI has yielded more accurate data than PET/CT and SPECT/CT.